First Principles Calculations of Atomic and Electronic Structure of Ti3+Al- and Ti2+Al-Doped YAlO3 - Piskunov, Sergei; Gopejenko, Aleksejs; Pankratov, Vladimir; Isakovica, Inta; Chong-Geng, Ma; Brik, Mikhail G.; Piasecki, Michal; Popov, Anatoli I. (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
In this paper, the density functional theory accompanied with linear combination of atomic orbitals (LCAO) method is applied to study the atomic and electronic structure of the Ti3+ and Ti2+ ions substituted for the host Al atom in orthorhombic Pbnm bulk YAlO3 crystals. The disordered crystalline structure of YAlO3 was modelled in a large supercell containing 160 atoms, allowing simulation of a substitutional dopant with a concentration of about 3%. In the case of the Ti2+-doped YAlO3, compensated F-center (oxygen vacancy with two trapped electrons) is inserted close to the Ti to make the unit cell neutral. Changes of the interatomic distances and angles between the chemical bonds in the defect-containing lattices were analyzed and quantified. The positions of various defect levels in the host band gap were determined. © 2021 by the authors. Licensee MDPI, Basel, Switzerland. Published under the CC BY 4.0 license.
M.G.B. appreciates support from the Chongqing Recruitment Program for 100 Overseas Innovative Talents (grant no. 2015013), the Program for the Foreign Experts (grant no. W2017011), Wenfeng High-end Talents Project (grant no. W2016-01) offered by the Chongqing University of Posts and Telecommunications (CQUPT), Estonian Research Council grant PUT PRG111, European Regional Development Fund (TK141), and NCN project 2018/31/B/ST4/00924. This study was supported by a grant from Latvian Research Council No. LZP-2018/1-0214 (for AIP). Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Program H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under Grant Agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES; Ab initio modelling; Electronic structure; Substitutional point defects; Ti-dopant; YAlO3